Lean Sourcing and Performance of Manufacturing Firms in Kenya - Njagi, Cosmus Mutwiri; Osoro , Anthony; Nyangau , Samson (International Journal of Supply Chain and Logistics, 2025)
Purpose: This study sought to examine the influence of lean souring on performance of manufacturing firms in Kenya. The study also sought to find out the moderating effect of ICT adoption on the relationship between lean souring and performance of manufacturing firms in Kenya. The agency theory anchors these concepts. The information theory explains the role of ICT as a moderating variable. Methodology: The study adopted the cross-sectional research design since it’s interested in establishing relationships without interfering with variables. In this study the unit of analysis was the 46 registered manufacturing firms while the unit of observation in this study was management employees in the supply chain department, procurement department, IT department and finance department. The total target population was 1,104 respondents. The sample size was determined using the Taro Yamane Formulae which was formulated by Tara Yamane in 1967. Therefore, the sample size was 294. The study used purposive sampling to select the respondents. Data was collected using a structured questionnaire administered both on the online platforms and also face to face. The reliability of these instruments was assessed during the pilot study. A review by professionals helped in refining the instruments to make the results reliable and valid. The data was analyzed using the SPSS software. The analytical model included descriptive statistics, correlation analysis, regression analysis and moderation analysis using the SPSS software. Findings: The study found that lean souring has a positive and significant effect on performance of manufacturing firms in Kenya. The study also found that ICT adoption has a positive and significant moderating effect on the relationship between lean souring and performance of manufacturing firms in Kenya. Unique Contribution to Theory, Practice and Policy: From the findings the study recommends that the management of manufacturing firms in Kenya to provide comprehensive training on lean sourcing principles and methodologies across all levels of the organization. Actively implement lean sourcing practices, with a specific focus on bulk sourcing, item categorization, and supplier development.